COVID-19-associated hospitalizations among children less than 12 years of age in the United States. (31st December 2022) - Di Fusco, Manuela; Vaghela, Shailja; Moran, Mary M.; Lin, Jay; Atwell, Jessica E.; Malhotra, Deepa; Scassellati Sforzolini, Thomas; Cane, Alejandro; Nguyen, Jennifer L.; McGrath, Leah J.
Abstract: Objectives: To describe the characteristics, healthcare resource use and costs associated with initial hospitalization and readmissions among pediatric patients with COVID-19 in the US. Methods: Hospitalized pediatric patients, 0–11 years of age, with a primary or secondary discharge diagnosis code for COVID-19 (ICD-10 code U07.1) were selected from 1 April 2020 to 30 September 2021 in the US Premier Healthcare Database Special Release (PHD SR). Patient characteristics, hospital length of stay (LOS), in-hospital mortality, hospital costs, hospital charges, and COVID-19-associated readmission outcomes were evaluated and stratified by age groups (0–4, 5–11), four COVID-19 disease progression states based on intensive care unit (ICU) and invasive mechanical ventilation (IMV) usage, and three sequential calendar periods. Sensitivity analyses were performed using the US HealthVerity claims database and restricting the analyses to the primary discharge code. Results: Among 4, 573 hospitalized pediatric patients aged 0–11 years, 68.0% were 0–4 years and 32.0% were 5–11 years, with a mean (median) age of 3.2 (1) years; 56.0% were male, and 67.2% were covered by Medicaid. Among the overall study population, 25.7% had immunocompromised condition(s), 23.1% were admitted to the ICU and 7.3% received IMV. The mean (median) hospital LOS was 4.3 (2) days, hospital costs and charges were 14, 760 (6, 164) and 58, 418 (21, 622), respectively; in-hospital mortality was 0.5%. LOS, costs, charges, and in-hospital mortality increased with ICU admission and/or IMV usage. In total, 2.1% had a COVID-19-associated readmission. Study outcomes appeared relatively more frequent and/or higher among those 5–11 than those 0–4. Results using the HealthVerity data source were generally consistent with main analyses. Limitations: This retrospective administrative database analysis relied on coding accuracy and inpatient admissions with validated hospital costs. Conclusions: These findings underscore that children aged 0–11 years can experience severe COVID-19 illness requiring hospitalization and substantial hospital resource use, further supporting recommendations for COVID-19 vaccination.